Analisis Komunikasi Bisnis Dalam Meningkatkan Penjualan UMKM Sishop_Id Pada Fitur Live Di Aplikasi Shopee - Sinta Puspita Sari; Muhammad Rizal Fadilah; Rul Fahmi; Ricky Firmansyah (Student Research Journal, 2023)
At this time technology is advancing rapidly, especially in the advancement of digital platforms. The impact of technological advances is felt by people in various lives, one of which is online shopping. How effective promotional messages can increase sales of Sishop_Id MSMEs through the live feature in the Shopee application The purpose of the research is to analyze business communication in increasing sales of Sishop_Id MSMEs on the live feature in the Shopee application to understand how the business communication strategy carried out by Sishop_Id in Shopee's live feature can affect the increase in sales of MSME products offered by Sishop_Id. The methodology used in this research is a qualitative approach with a descriptive approach. Based on the results of interviews we conducted with Sishop_id MSME actors, this business was started by several students who thought about how to get additional income. in December 2022 they started a business with small capital they were able to create a business which in the end they chose a business idea in the fashion sector, especially kameja, culottes, crop korean, outer and others. Sishop_id experienced an increase in sales of their products after using the live feature on Shopee. Initially, only 1-2 people bought their products, but now there are 5-10 people who buy their products. Developing a broader marketing strategy In addition to using discounts and vouchers, it is better to develop a broader marketing strategy such as providing gifts or merchandise for consumers who buy a certain amount of products or collaborating with influencers to promote Sishop_id products. This can increase awareness and trustworthiness of the online store. The use of the shopee live feature in Sishop_id MSMEs has experienced a significant increase in sales in the products sold.